O organizar das práticas e a produção de histórias da área de visitação do Palácio Anchieta - Carlini, Tatiane dos Santos (2023)
This research aims to understand the organization of practices and the production of histories in the visiting area of the Palácio Anchieta. The research sought to understand the resignification of institutional spaces and the production of histories from the appropriation of everyday practices. To achieve this objective, I sought to identify and understand the daily practices of the organization's participants based on Michel de Certeau's conception of practice. From the theoretical basis, I searched in the field to identify the practices and histories that manifest themselves in the visitation area of the Palácio Anchieta from the resignification of spaces. Field immersion was based on observation, which ranged from participant to non-participant, and data analysis was performed using content analysis, which gave rise to two categories: 1) the redefinition of space based on the appropriation of practices; 2) the recovery of the ordinary in history through practices. The results pointed to a redefinition of spaces and the emergence of new histories from small transgressions in everyday practices, evidenced from the disputes between the official history and the stories that emerged from the practices of the holidays between the mediators and visitors.